Public Finance - Planning Commission (Planning Commission, 1939)
Since this Reference was made, the economic, financial and political conditions and circumstances of the country as a whole have been so radically altered that it is impossible to outline any dependable picture of the country’s financial position and possibilities, with particular regard to the use of Public Finance in carrying out a nation-wide comprehensive plan of progressive development. Six years of a World War cannot but leave their mark on the public economy of any country, and much more so on the national economy of a country which had made War effort on the scale that India had done. But quite apart from this, the country has ceased to be a dependency of Britain, and attained, virtually speaking, her national independence, which cannot but affect vitally and at the very root her financial system, and its capacity to help in carrying out a comprehensive National Plan.
National Planning Committee
National Planning Committee